2022
DOI: 10.1101/2022.03.09.22272162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary Rasch analysis of the Multidimensional Assessment of Interoceptive Awareness in adults with stroke

Abstract: Purpose The Multidimensional Assessment of Interoceptive Awareness (MAIA) measures interoceptive body awareness, which includes aspects such as attention regulation, self-regulation, and body listening. Our purpose was to validate the MAIA in adults with stroke using Rasch Measurement Theory. Methods The original MAIA has 32 items grouped into eight separately scored subscales that measure aspects of body awareness. Using Rasch Measurement Theory, we evaluated the unidimensionality of the entire scale and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…This might be attributed to the change from a 6‐point to a 5‐point response scale in our study. Effects of response format changes on endorsability will require empirical scrutiny through inspection with item response methods in a future study (e.g., Blackwood et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the change from a 6‐point to a 5‐point response scale in our study. Effects of response format changes on endorsability will require empirical scrutiny through inspection with item response methods in a future study (e.g., Blackwood et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These items were item 5, "I do not notice physical tension or discomfort until they become more severe"; item 16, "I can maintain awareness of my whole body even when a part of me is in pain or discomfort"; and item 23, "When I feel overwhelmed, I can find a calm place inside. " This exclusion was supported by multiple studies, which concluded that the MAIA employs precise and effective items to ensure accurate targeting and reliability (Blackwood et al, 2023).…”
Section: Introductionmentioning
confidence: 99%